Supercapacitors based on carbon or pseudocapacitive materials - Simon, P. (Patrice), 1969-; Brousse, Thierry; Favier, Frédéric (Energy storage -- batteries, supercapacitors set ;, 2017)
"Electrochemical capacitors are electrochemical energy storage devices able to quickly deliver or store large quantities of energy. They have stimulated numerous innovations throughout the last 20 years and are now implemented in many fields. Supercapacitors Based on Carbon or Pseudocapacitive Materials provides the scientific basis for a better understanding of the characteristics and performance of electrochemical capacitors based on electrochemical double layer electrodes or pseudocapacitive materials, as well as providing information on the design and conception of new devices such as lithium-ion capacitors. This book details the various applications of supercapacitors, ranging from power electronics and stationary use, to transportation (hybrid vehicles, trams, planes, etc.). They are increasingly used in the automotive sector, especially as part of stop/start systems that have allowed for energy recovery through braking and reduced fuel consumption."--Publisher description.